If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3 + k) = 2 (3 * 2 + k * 2) = 2 (6 + 2k) = 2 Solving 6 + 2k = 2 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 2k = 2 + -6 Combine like terms: 6 + -6 = 0 0 + 2k = 2 + -6 2k = 2 + -6 Combine like terms: 2 + -6 = -4 2k = -4 Divide each side by '2'. k = -2 Simplifying k = -2
| 8y+328=4y | | 3x+9=42 | | 3(-2-4)=2(5-2+1) | | 3c^2+25c+50=0 | | 11x-6=3x^2 | | 5=x+10 | | x^2-4x-21=fector | | x^4-4x^3-12x^2=0 | | 4/12= | | 5x+7.2=4x | | P^2+2p-8= | | 4x^2-24x+27=0 | | 5v^2+3=-8v | | w+16=-8 | | 3X+47=0 | | r^2+2rh-35h^2= | | 4x-5=7(x-5) | | 3x-4y=27 | | -19n=323 | | -(x+3)+2(x+7)= | | 3+5u=-27 | | 8s^2+4s= | | 8y-3=4y+15 | | 2x^2-14x+3=0 | | 14r=126 | | 6y+4x=44 | | 0=25x^2+7x-18 | | -3(x-4)-(2x-7)= | | 8y-3=4y+5 | | 8x+8=6x+34 | | 4(x+3)=2x-2 | | 3(4x-1)=39 |